RURAL COMMUNITY UNDERSTANDING OF THE BENEFITS OF HEALTH INSURANCE IN INDONESIA: LITERATURE REVIEW - Safira, Meylia; Nurdin, Ambia (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
The knowledge of rural communities regarding health insurance is still limited, leading them to use insurance less compared to urban residents. This lack of understanding is related to the characteristics of rural communities, which are heavily influenced by religious factors in their perception of insurance laws. This study aims to analyze and understand effective and efficient methods of socialization to reach all groups and layers of society. The study is a literature review that cites several online sources such as Google Scholar and Garuda, using keywords such as